Hemoglobinopathies and thalassemia screening among Senoi Orang Asli in Peninsular Malaysia - Rong D.K.X.; Ismail E.; Sabudin R.Z.A.R.; Hussin N.H.; Othman A. (American Institute of Physics Inc., 2024)
Orang Asli are the minority indigenous people in Peninsular Malaysia and can be divided into 3 main groups (Negrito, Senoi and Proto Malay) with different six sub-ethnics under each group. Within the Senoi group, the six sub-ethnics are sub-ethnic Mah Meri, Semoq Beri, Che Wong, Jah Hut, Semai and Temiar. This study was aimed to investigate the current prevalence of ?- and ?-thalassemia and hemoglobinopathies and their mutation types among all six sub-ethnics of Senoi Orang Asli. Blood samples from 685 Senoi participants were collected and sent immediately for routine full blood count analysis and hemoglobin sub-typing. Of 378 subjects screened, 7 subjects were found to be Hemoglobin E (HbE) beta thalassemia carriers, 13 beta thalassaemic, 35 Hemoglobin Constant Spring (HbCS) carriers, 6 compound HbE and HbCS carriers, 32 with HbE disease and 163 HbE heterozygote carriers. The findings of high HbE among Temiars and Jah Huts and high HbCS exclusively in Jah Huts in this study suggest distinct differences across sub-ethnics under Senoi group. Understanding of prevalence and wide spectrum of thalassemia and hemoglobinopathies among Senoi and Orang Asli is essential for national thalassaemia awareness and prevention program, especially in Orang Asli communities. 2015 AIP Publishing LLC.